2017
DOI: 10.22323/2.16010201
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer recruitment and retention in online citizen science projects using marketing strategies: lessons from Season Spotter

Abstract: Citizen science continues to grow, potentially increasing competition among projects to recruit and retain volunteers interested in participating. Using web analytics, we examined the ability of a marketing campaign to broaden project awareness, while driving engagement and retention in an online, crowdsourced project. The campaign challenged audiences to support the classification of >9,000 pairs of images. The campaign was successful due to increased engagement, but it did not increase the time participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 31 publications
6
42
1
Order By: Relevance
“…Although recruiting messages are the first point of contact with new participants, researchers do not seem to have identified which messages are more effective in attracting participants. Studies by Robson et al [2013] and Crall et al [2017] have examined the efficacy of different media in recruiting participants, e.g., by comparing traditional media and social networking, but not the efficacy of different messages.…”
Section: Introductionmentioning
confidence: 99%
“…Although recruiting messages are the first point of contact with new participants, researchers do not seem to have identified which messages are more effective in attracting participants. Studies by Robson et al [2013] and Crall et al [2017] have examined the efficacy of different media in recruiting participants, e.g., by comparing traditional media and social networking, but not the efficacy of different messages.…”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of studies on awareness of IPFPs. However, recent studies have reported the effect of marketing communication efforts on awareness on a variety of services, such as for fund-raising activities (Veríssimo et al, 2017), the use of academic e-books by library users (Raynard, 2017), and volunteer recruitment and retention (Crall et al, 2017). Likewise, the impact of social influence on awareness was also reported in the literature, such as Hutter et al (2013) who investigated the impact of social media on brand awareness, and Gaspar et al (2016) who examined the effect of social influence on eating awareness among children.…”
Section: Structural Modelmentioning
confidence: 99%
“…Clary, Snyder, Ridge, Miene, and Haugen (1994) and Clary et al (1998) have demonstrated that potential volunteers are more responsive to recruitment messages that match their personally relevant motivations. These recommendations have been affirmed by others as a way to effectively recruit volunteers in a variety of contexts, including youth sports (Busser & Carruthers, 2010), citizen science programs (Crall et al, 2017), and emergency response (Haug & Gaskins, 2012); and as a way to appeal to the interests of young people (Shields, 2009). Furthermore, volunteers whose motivations match their experience are likely to be more satisfied, volunteer for longer periods, and volunteer again (Bussell & Forbes, 2002; Clary et al, 1998; Clary, Snyder, & Ridge, 1992; Clary, Snyder, & Stukas, 1996; Gage & Thapa, 2012; Houle, Sagarin, & Kaplan, 2005; Martinez & McMullin, 2004; Stukas, Daly, & Clary, 2006).…”
Section: Introductionmentioning
confidence: 99%